ENTREPRENEURSHIP IN UKRAINE: DEVELOPMENT DYNAMICS AND THE ROLE OF STANDARDIZED DECISIONS - Kobernyk, Ivan V. (Journal of Strategic Economic Research, 2025)
The article analyzes the significance of entrepreneurship for economic growth and social development. The entrepreneur is considered a key participant in the economic process, whose decisions and actions influence the dynamics of a country's development, the formation of gross domestic product, and other important economic indicators. In modern conditions, entrepreneurial activity goes beyond mere commercial interest-it also acquires social and psychological dimensions, influencing the structure of social relations and contributing to their transformation. The article also highlights how entrepreneurship contributes to the restructuring of economic mechanisms and how successful businesses should consider not only profitability but also the interests of all stakeholders: investors, employees, consumers, and the state. In the Ukrainian context, modern entrepreneurship is characterized by the expansion of activity areas and the increase in the number of managerial decisions made at different organizational levels. Special attention is given to the need to improve the professional training of personnel and the development of interaction between them to ensure effective decision-making. Among the identified problems is the limitation of traditional forms of professional development, which often do not meet the pace of modern development and changes in management approaches. To address these challenges, the creation of specialized databases of typical managerial decisions is proposed. These would accelerate the process of making effective decisions in typical situations. Such solutions would reduce risks and improve the organization of production and commercial processes. Additionally, the article emphasizes the relevance of integrating such solutions into educational programs, which would help improve the training level of future managers and specialists in the entrepreneurial field.